Healthcare workers' perceptions and attitudes towards the UK's COVID-19 vaccination programme: a rapid qualitative appraisal. Issue 2 (15th February 2022) - Manby, Louisa; Dowrick, Anna; Karia, Amelia; Maio, Laura; Buck, Caroline; Singleton, Georgina; Lewis-Jackson, Sasha; Uddin, Inayah; Vanderslott, Samantha; Martin, Sam; Vindrola-Padros, Cecilia
Abstract : Objectives: While there is research relating to perceptions of vaccines among healthcare workers (HCWs), the evidence base in relation to COVID-19 remains limited. The aim of this study was to explore HCWs' perceptions and attitudes towards vaccines and the COVID-19 vaccination programme in the UK, including their expectations and views on promoting vaccination to others. Design: This study was designed as a rapid qualitative appraisal, integrating data from a review of UK policies and guidance on COVID-19 vaccination with data from in-depth semistructured telephone interviews with frontline HCWs in the UK. Data were analysed using framework analysis. Participants: Interviews were carried out with a purposive sample of HCWs from two large London-based hospital Trusts (n=24) and 24 government policies, and guidelines on the vaccination programme were reviewed. Results: The level of uncertainty about the long-term safety of vaccines and efficacy against mutant strains made it difficult for HCWs to balance the benefits against the risks of vaccination. HCWs felt that government decisions on vaccine rollout had not been supported by evidence-based science, and this impacted their level of trust and confidence in the programme. The spread of misinformation online also impacted HCWs' attitudes towards vaccination, particularly among junior level and black, Asian and minority ethnic (BAME) HCWs. Most HCWs felt encouraged to promote vaccination to their patients, and the majority said they would advocate vaccination or engage in conversations about vaccination with others when relevant. Conclusion: In order to improve HCWs' trust and confidence in the UK's COVID-19 vaccination programme, there needs to be clarity about what is known and not known about the vaccines and transparency around the evidence-base supporting government decisions on vaccine rollout. Effort is also needed to dispel the spread of vaccine-related misinformation online and to address specific concerns, particularly among BAME and junior-level HCWs.